Kaidah fiqh sebagai landasan etika muamalah bisnis islami di era globalisasi - Maulana, Ahmad Faiz Ridwan (Maliki Interdisciplinary Journal, 2025)
Business globalization demands the application of ethics that can ensure equality, transparency, and fairness in cross-border economic transactions. In this context, fiqh muamalah, as a guideline for Islamic business ethics, provides relevant principles for maintaining social justice, economic responsibility, and sustainability in the global business world. Fiqh muamalah includes rules regarding buying and selling, renting, lending and borrowing, as well as principles such as justice (al-'adl), willingness (ar-ridha), and clarity (al-bayan). Although fiqh muamalah has long been known in the context of everyday Muslim life, its application in international business is still limited. This study aims to identify the principles of fiqh muamalah relevant to global business ethics, with a focus on the application of sharia principles in international transactions and efforts to create a just and transparent economic system. This study uses a qualitative and comparative approach, comparing fiqh muamalah theories in classical literature with emerging global business practices. It is hoped that this research can contribute to the development of fiqh muamalah literature and its application in international business, as well as provide practical guidance for Muslim entrepreneurs in integrating Islamic principles in global business transactions.